Degrowth Theory and the Language Teaching-Learning Process - Luis Guillermo Barrantes-Montero (Universidad Nacional, Costa Rica, 2014)
This paper aims to show how the consecutive crises faced by those societies ruled by a market economy pervade all areas of generation and transfer of knowledge. Such crises also demand serious redefinitions from societies in both their epistemological assumptions and their substantive actions. More precisely, the processes of language teaching and learning are viewed ​​in the light of the Degrowth Theory, as an alternative approach to the trends of using the teaching of languages ​​as a means of legitimizing the production-consumption vortex that threatens the global future.